Monoclonal Antibody Therapies for Hematological Malignancies: Not Just Lineage-Specific Targets - Cuesta-Mateos, Carlos; Alcaraz-Serna, Ana; Somovilla-Crespo, Beatriz; Muñoz-Calleja, Cecilia (Frontiers in Immunology, 2018)
Today, monoclonal antibodies (mAbs) are a widespread and necessary tool for biomedical science. In the hematological cancer field, since rituximab became the first mAb approved by the FDA for the treatment of B-cell malignancies, a number of effective mAbs targeting lineage-specific antigens (LSA) have been successfully developed. Non-lineage related antigens (NLSAs) are molecules which are not restricted to specific leukocyte subsets or tissues, but play relevant pathogenic roles in blood cancers including the development, proliferation, survival and refractoriness to therapy of tumor cells. In consequence, efforts to target NLSAs have resulted in a plethora of mAbs -marketed or in development- to achieve different goals like neutralizing oncogenic pathways, blocking tumor-related chemotactic pathways, mobilizing malignant cells from tumor microenvironment (TME) to peripheral blood, modulating immune-checkpoints, or delivering cytotoxic drugs into tumor cells. Here, we extensively review several novel mAbs directed against NLSAs undergoing clinical evaluation for treating hematological malignancies. The review focuses on the structure of these antibodies, proposed mechanisms of action (MOA), efficacy and safety profile in clinical studies, and their potential applications in the treatment of hematological malignancies.